2010
DOI: 10.1002/jmv.21739
|View full text |Cite
|
Sign up to set email alerts
|

Geographical differences in the proportion of human group A rotavirus strains within New Zealand during one epidemic season

Abstract: The prospect of future rotavirus vaccine programs means it is important to understand rotavirus strain diversity within New Zealand, especially if this was to influence vaccine effectiveness. The G-genotype of 359 group A rotavirus strains isolated from 416 stool samples collected from June 2005 to May 2006 (inclusive) from children less than 5 years of age in multiple centers throughout New Zealand was determined. G1 was the dominant circulating strain (55.8%) followed by G4 (21.4%), G3 (3.4%), G9 (3.4%) G2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, this emergent BoRVA genotype has already been diagnosed in surveys done in calves from Europe and Argentina, and sheep in India (Monini et al 2008, Gazal et al 2012, Midgley et al 2012, Badaracco et al 2013. Moreover, the G6P[11] genotype has been identified in RVA strains from human hosts from Africa (Sherif et al 2011), Asia (Yamamoto et al 2011), Europe (De Grazia et al 2011, Steyer et al 2013, Oceania (Chandrahasen et al 2010), and America (Brazil) (Munford et al 2007, Martini et al 2008. Moreover, cattle can be a reservoir of rotavirus G6P[11] genotype for human hosts (Martella et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, this emergent BoRVA genotype has already been diagnosed in surveys done in calves from Europe and Argentina, and sheep in India (Monini et al 2008, Gazal et al 2012, Midgley et al 2012, Badaracco et al 2013. Moreover, the G6P[11] genotype has been identified in RVA strains from human hosts from Africa (Sherif et al 2011), Asia (Yamamoto et al 2011), Europe (De Grazia et al 2011, Steyer et al 2013, Oceania (Chandrahasen et al 2010), and America (Brazil) (Munford et al 2007, Martini et al 2008. Moreover, cattle can be a reservoir of rotavirus G6P[11] genotype for human hosts (Martella et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…But from the African continent, G12 in combination with P[6] or P[8] has been reported from only South Africa, Malawi and Nigeria [18][20]. Rotavirus G8 genotype has been reported from humans worldwide with high prevalence in some African countries [17], [21][28].…”
Section: Introductionmentioning
confidence: 99%
“…Genotype G8, one of the most common G genotypes found in cattle [Estes and Kapikian, 2007; Martella et al, 2009], was first reported from a child with diarrhea in Indonesia [Hasegawa et al, 1984]. Thereafter, G8 strains have been reported from humans in different countries worldwide [O'Halloran et al, 2000; Gentsch et al, 2005; Santos and Hoshino, 2005; Matthijnssens et al, 2006b; Steyer et al, 2007; Kiulia et al, 2008; Le et al, 2008; Banyai et al, 2009, 2010; Esona et al, 2009; Pietsch et al, 2009; Chandrahasen et al, 2010], with significant rates of detection in some African nations [Santos and Hoshino, 2005; Kiulia et al, 2008; Esona et al, 2010; Nokes et al, 2010]. To date, human G8 strains have been reported in association with a wide variety of P genotypes (P[1], P[2], P[4], P[6], P[8], P[10], P[11], or P[14]) [Santos and Hoshino, 2005; Pietsch et al, 2009; Banyai et al, 2009, 2010; Esona et al, 2009, 2010; Nokes et al, 2010; Nyangao et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Genotype G8, one of the most common G genotypes found in cattle [Estes and Kapikian, 2007;Martella et al, 2009], was first reported from a child with diarrhea in Indonesia [Hasegawa et al, 1984]. Thereafter, G8 strains have been reported from humans in different countries worldwide [O'Halloran et al, 2000;Gentsch et al, 2005;Santos and Hoshino, 2005;Matthijnssens et al, 2006b;Steyer et al, 2007;Kiulia et al, 2008;Le et al, 2008;Banyai et al, 2009Banyai et al, , 2010Esona et al, 2009;Pietsch et al, 2009;Chandrahasen et al, 2010], with significant rates of detection in some African nations [Santos and Hoshino, 2005;Kiulia et al, 2008;Esona et al, 2010;Nokes et al, 2010] [Santos and Hoshino, 2005;Pietsch et al, 2009;Banyai et al, 2009Banyai et al, , 2010Esona et al, 2009Esona et al, , 2010Nokes et al, 2010;Nyangao et al, 2010]. These observations suggested that most of the human G8 strains might have originated from complex reassortment events involving human and/or animal rotaviruses or animal-to-human interspecies transmission events [Santos and Hoshino, 2005].…”
Section: Introductionmentioning
confidence: 99%